SYNTHESIS OF PVDF-HFP/MGO NANOFIBER COMPOSITES USING ELECTROSPINNING METHOD AND ITS APPLICATION AS ARSENIC ADSORBENT - Rinovian, Asnan
Arsenic present in drinking water can pose a risk to humans. Arsenic can be naturally occurring in groundwater or as a result of contamination from industrial, mining, and agricultural activities. Various methods have been developed to remove arsenic, including chemical precipitation, coagulation and flocculation, biological processes, ion exchange, oxidation processes, and adsorption. The weaknesses of chemical precipitation and coagulation methods often fail to meet the desired standards. Ion exchange and oxidation processes are considered expensive methods. Therefore, adsorption has become an attractive method to develop due to its advantages such as good efficiency, easy operation, and relatively low cost. Magnesium oxide nanoparticles (MgO NPs) are materials that can function as arsenic adsorbents. However, in the adsorption techniques developed, there is a problem of separating the adsorbent from the water after the adsorption process is completed. Therefore, many studies have been conducted to overcome this issue, one of which is by compositing MgO NPs with copolymer nanofibers such as PVDF-HFP (polyvinylidene fluoride-co-hexafluoropropylene). In this study, the synthesis of PVDF-HFP/MgO nanofiber composite is conducted with the aim of enhancing its adsorption capacity and facilitating the separation process of the adsorbent from water. MgO nanoparticles are synthesized from seawater bittern, which is a byproduct of traditional salt production, using the precipitation method. Thus, this research involves the utilization of waste (seawater bittern) to produce a material that is more beneficial and can add value to the byproduct. MgO nanoparticles, PVDF-HFP nanofibers, and PVDF-HFP/MgO nanofiber composites synthesized have been characterized using XRD, FTIR, SEM-EDS, TEM, BET, and TGA. Batch adsorption tests were then conducted on each sample (MgO nanoparticles, PVDF-HFP nanofibers, and PVDF-HFP/MgO nanofiber composites). The adsorption capacity was tested by varying parameters such as pH, contact time, adsorbent mass, and initial arsenic concentration. Additionally, the stability of the adsorbent was tested at various pH values. The results showed that the maximum adsorption for As(V) was 41.91 mg/g for PVDF-HFP/MgO 30% (w/w), equivalent to 181.60 mg/g if the divider is the weight of MgO NPs in the nanofiber under optimum conditions at pH 11, contact time of 420 minutes, and adsorbent mass of 0.0125 g. Compositing MgO NPs into the nanofiber matrix can enhance its stability, leading to an increased adsorption capacity. The adsorption kinetics followed a pseudo-second-order model, and the adsorption isotherm followed the Sips isotherm model. This study demonstrates the potential use of PVDF-HFP/MgO nanofiber composites for treating arsenic-contaminated water and providing commercial benefits to seawater bittern by using it as a precursor for functional nanomaterial production.